2003
DOI: 10.1542/peds.111.1.6
|View full text |Cite
|
Sign up to set email alerts
|

Errors in Medical Interpretation and Their Potential Clinical Consequences in Pediatric Encounters

Abstract: ABSTRACT. Background. About 19 million people in the United States are limited in English proficiency, but little is known about the frequency and potential clinical consequences of errors in medical interpretation.Objectives. To determine the frequency, categories, and potential clinical consequences of errors in medical interpretation.Methods. During a 7-month period, we audiotaped and transcribed pediatric encounters in a hospital outpatient clinic in which a Spanish interpreter was used. For each transcrip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
463
1
16

Year Published

2004
2004
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 908 publications
(493 citation statements)
references
References 33 publications
13
463
1
16
Order By: Relevance
“…Language barriers encountered in the care of patients with limited English proficiency (LEP), a growing segment of the U.S. population 2 , adversely affect healthcare quality. Patients with LEP may have decreased access to acute care and preventive services [3][4][5][6] , decreased satisfaction with care 7,8 , poor understanding of instructions or medications 9,10 , longer hospital stays 11 , and an increased risk of medical errors and misdiagnoses [12][13][14][15][16] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Language barriers encountered in the care of patients with limited English proficiency (LEP), a growing segment of the U.S. population 2 , adversely affect healthcare quality. Patients with LEP may have decreased access to acute care and preventive services [3][4][5][6] , decreased satisfaction with care 7,8 , poor understanding of instructions or medications 9,10 , longer hospital stays 11 , and an increased risk of medical errors and misdiagnoses [12][13][14][15][16] .…”
Section: Introductionmentioning
confidence: 99%
“…The use of professional interpreters improves the quality of care for patients with LEP, resulting in higher patient satisfaction 17 , fewer errors in communication 14 , reduced disparities in utilization of services 18 , and improved clinical outcomes 19 . Despite accumulating evidence of the benefits of professional interpreter use, recent studies suggest that that they are underused by physicians [20][21][22][23] .…”
Section: Introductionmentioning
confidence: 99%
“…Clients often prefer that a friend or relative who they know and trust acts as an interpreter, rather than as a professional (Parnes and Westfall, 2003;Xuo and Fagan, 1999). Clinicians report concerns that untrained interpreters such as the patients' relatives or friends may not translate sensitive or technical information appropriately, accurately, or at all, and their use may raise issues of confidentiality (Flores et al, 2003;Phelan and Parkman, 1995;Shaw, 2003a). Using trained medical interpreters does not necessarily eliminate miscommunication (Brafman, 1995;Kaufert and Putsch, 1997;Phelan and Parkman, 1995;Schaafsma et al, 2002) and may cause anxiety to the patient, especially where the interpreter's role has been inadequately negotiated beforehand (Parnes and Westfall, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Ad hoc interpreters can misinterpret or omit up to half of physicians' questions, are more likely to commit errors with clinical significance, have a higher risk of not mentioning medication side effects, and may ignore embarrassing issues (especially when children are used to interpret). 3,6,7 From an economical standpoint, it has been found that LEP patients stay in the hospital between 0.7 and 4.3 days longer than English speaking patients with similar conditions. 8 In addition non-English speaking patient have a higher 30-day readmission rate compared to their English speaking counterparts.…”
mentioning
confidence: 99%